Unilateral mesial temporal atrophy after a systemic insult as a possible etiology of refractory temporal lobe epilepsy: case report Esclerose mesial temporal unilateral após insulto sistêmico como possível etiologia de epilepsia refratária do lobo temporal: relato de caso - Arthur Cukiert; Mario Sergio Duarte Andrioli; Ana Regina Caner-Cukiert (Arquivos de Neuro-Psiquiatria)
Mesial temporal sclerosis is the main pathological substrate present in refractory temporal lobe epilepsy and its presence is often related to the occurrence of febrile seizures in infancy. There is an on-going discussion on the nature of mesial temporal sclerosis as it related to epilepsy: cause or consequence. A previously normal child developed hyperosmolar coma after abdominal surgery at the age of 6. Three months afterwards he developed simple and complex partial seizures with an increasing frequency and refractory to multiple mono-and polytherapic drug regimens. He was evaluated for surgery at the age of 13. Ictal and interictal recordings showed left temporal lobe abnormalities. Early CT scaning suggested left temporal atrophy. MRI showed mesial temporal sclerosis. Neuropsichological testing showed verbal memory deficits and he passed a left carotid artery amytal injection. He was submitted to a cortico-amygdalo-hippocampectomy and has been seizure-free since then. The clinical data obtained from this patient suggest that at least in this case mesial temporal sclerosis would be related to the cause of epilepsy and not resultant from repeated seizure activity. A esclerose mesial temporal é o principal substrato anatomo-patológico envolvido na epilepsia refratária do lobo temporal e está frequentemente associada à ocorrência de convulsões febris na infância. Persiste até o momento intensa discussão se a esclerose mesial seria causa ou consequência da síndrome epiléptica. Uma criança previamente normal, desenvolveu coma hiperosmolar após intercorrência em cirurgia abdominal aos 6 anos de idade. Após 3 meses iniciaram-se crises parciais simples e complexas em frequência ascendente e refratárias a múltiplos esquemas terapêuticos em mono- e politerapia. Ele realizou investigação pré-operatória para epilepsia aos 13 anos de idade. Registros eletrencefalográficos de superfície ictais e interictais mostraram anormalidades temporais esquerdas. TC de crânio antiga, próxima ao insulto sistêmico, já sugeria atrofia do lobo temporal. RMN demonstrou esclerose mesial temporal. Testagem neuropsicológica mostrou déficit de memória verbal e este paciente apresentou o padrão passa-ipsi/falha contralateralmente no teste de amital sódico. Ele foi submetido a córtico-amígdalo-hipocampectomia e está sem crises desde então. Os achados anátomo-patológicos são de esclerose mesial. Os dados obtidos neste paciente sugerem que, ao menos neste caso, a esclerose mesial temporal está possivelmente relacionada à causa da epilepsia e não à presença de crises recorrentes.